COVID-19 Concerns Among Old Age Psychiatric In- and Out-Patients and the Employees Caring for Them, a Preliminary Study - Korsnes, Maria Stylianou; Grødal, Elsa; Kjellén, Elisabeth; Kaspersen, Tone M. C.; Gjellesvik, Kristin B.; Benth, Jūratė Šaltytė; McPherson, Bodil A. (Frontiers in Psychiatry, 2020)
A questionnaire was administered to 14 patients admitted at the Department of Old Age Psychiatric 24-hour unit at Oslo University Hospital with questions about experiences and fears regarding Covid-19. A similar adjusted questionnaire was administered to 19 outpatients. The purpose was to investigate if the patients had fears, anxieties, and quality of life issues related to Covid-19 that could affect their treatment. A quest back questionnaire with similar questions about patient care and work conditions was sent to the personnel working with these patients, and 46 of 81 responded. Most patients welcomed the strict measures that were applied, including a visitation ban for inpatients and a reduction in consultations for the outpatients. Most patients reported that they were not very scared of getting Covid-19, nor did many believe that they would die if they were infected. A minority of patients reported being very worried. The patients also differed on other issues related to the Covid-19 situation. A minority were negative to the interventions, rules, and regulations, and/or considered the risk of infection to be elevated at the clinic, and/or that the quality of their daily life was negatively impacted. Employees more often than patients were concerned about the Covid-19 influence on their health. They were also concerned about being at work amid the crisis. About half of their comments were related to the fear of inadvertently infecting patients with Covid-19. Also, a majority complained about aspects related to the implemented Covid-19 guidelines. This study is explorative in nature, mainly due to its small sample size, which makes it difficult to draw conclusions from the results. However, the results imply a need for addressing the Covid-19 concerns of both patients and employees, to prevent potential negative effects on treatment and overall life quality. Future research should investigate the self-reported effects of the pandemic situation on a larger sample size of elderly psychiatric patients.